(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Background & Aims: Spinal anaesthesia is popular procedure for abdomen and lower limb surgeries. Sympathetic blockade and BJR are important causes for hypotension and Bradycardia following spinal anaesthesia. Bezold Jarisch reflex (BJR) is mediated by peripheral serotonin receptors of the 5-HT3 type. The aim of the study was to compare prophylactic intravenous inj. Granisetron and inj. Ondansetron for the prevention of spinal anaesthesia induced hypotension and bradycardia to verify the hypothesis that blockade of 5HT3 serotonin receptors by both drugs might reduce hypotension and bradycardia. Material & Methods: A Total 104 patients with ASA grade I, II, aged 18-60 years, either gender, weighing of 40-60 kg were divided into two groups (52 patients in each group). Group A received Inj. Ondansetron 4 mg intravenously and Group B received Inj. Granisetron 1 mg intravenously 5 mins before spinal anaesthesia. SBP, DBP, MAP, PR, SpO2 recorded at basal, 5mins intervals for the first 30minutes,10 mins interval up to 1 hour, 15mins interval till end of surgery. Adverse events were also noted. Requirement of total dose of Atropine and Mephentermine was measured. Results: There was statistically significant difference of SBP between group A and group B at 5, 10,15,20,25,30 minutes (p<0.05), and MAP at 10,15,20,25minutes (p<0.05). There was statistically no significant difference of mean heart rate and DBP between group A and group B ( p > 0.05). Conclusion: Intravenous ondansetron is better in preventing hypotension than intravenous granisetron. Requirement of vasopressors was also reduced in the ondansetron group.